1998
DOI: 10.1111/j.1398-9995.1998.tb03778.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to antibiotics: T‐cell recognition of amoxicillin is HLA‐DR restricted and does not require antigen processing

Abstract: Allergic immune responses are initiated and maintained by T cells that recognize peptidic fragments of allergens in the context of major histocompatibility complex (MHC) class II molecules. An anomaly of this model exists in the T-cell response to haptens. Haptens are nonpeptide antigens that alone are too small to provoke an immune response. Nevertheless, T-cell responses to haptenic allergens clearly occur and are critically involved in allergic immune responses to drugs such as penicillin. Although the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…The skin and the lung are major sites for individuals to come into contact with haptens. Also, depending on the route, dose and frequency, hapten exposure may lead to a resolving contact hypersensitivity (poison ivy), 2,3 an allergic reaction (penicillin sensitivity), 4–6 or as we show here, a non‐resolving pulmonary interstitial fibrosis. Moreover, like viruses, haptens alter self‐antigens and therefore contribute to an ensuing immune response that may include autoimmune mechanisms 1,7–9 .…”
Section: Introductionmentioning
confidence: 62%
“…The skin and the lung are major sites for individuals to come into contact with haptens. Also, depending on the route, dose and frequency, hapten exposure may lead to a resolving contact hypersensitivity (poison ivy), 2,3 an allergic reaction (penicillin sensitivity), 4–6 or as we show here, a non‐resolving pulmonary interstitial fibrosis. Moreover, like viruses, haptens alter self‐antigens and therefore contribute to an ensuing immune response that may include autoimmune mechanisms 1,7–9 .…”
Section: Introductionmentioning
confidence: 62%
“…Interestingly, amoxicillin can bind directly to HLA molecules, and a hapten effect has been proposed in penicillin related allergies 24. However, as the combination of amoxicillin and clavulanate25 is more hepatotoxic than amoxicillin alone, and hepatotoxicity has been reported with clavulanate and ticarcillin,26 it is possible that clavulanate is the hepatotoxic component of co-amoxiclav.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that neither the hapten nor the pro‐hapten necessarily needs to undergo processing to become antigenic. This was illustrated by Horton et al ., who showed that amoxicillin, which forms a hapten by means of a covalent bond, is able to stimulate T cells in a processing‐independent manner by binding directly to peptide–MHC complexes.…”
Section: The Hapten/pro‐hapten Conceptmentioning
confidence: 99%